PENDIDIKAN POSITIVE PSYCHOLOGY PADA GURU SEKOLAH DASAR-MENENGAH SEBAGAI KONTRIBUSI TIM PELAYANAN PENDIDIKAN PAROKI NANDAN - Setiawan, Paulus; Harsoyo, Yohanes; Widiyanto, Yohannes Babtista Cahya; Setyapurnama, Yudi Santara; Murti, D. Sanusi SH; Kuswantoro, RB. Hendri (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Depression in students is an emotional condition that lasts a long time and affects the thoughts, feelings, and behavior of students. Depression can make students feel down, lose interest and joy, and reduce their academic achievement. Depression can be triggered by various factors, such as family history, physical health problems, trauma or childhood experiences, and stressful life events. The solution that can be taken as an effort to prevent depression is to carry out positive education, which is an implementation of positive psychology. Seminars or community service events that raise the theme of positive psychology aim to educate educators in positive education, thus making them realize students’ happiness. Further, the educators are expected to help the students to be able to control or reduce their level of depression so that they can improve their academic achievement, and even better, for the future of the students themselves. In this community service, the stages conducted were data collection through opinion polls, discussions, and evaluations. Based on the results of the evaluation through questionnaires, the material presented was well received by the participants, and this activity succeeded in increasing their knowledge and insight into positive education as an implementation of positive psychology.